Implementasi Manajemen Strategik di Madrasah - Dili Mutia Rahmah; M. Saleh; Muhyani Rizalie (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the implementation of strategic management in each educational unit, especially in madrasas. This research uses a qualitative approach, using interviews, observation, and documentation techniques. The data collected through various techniques is examined, and data reduction, data presentation, and data verification are carried out. The findings of the Strategic Environmental Analysis focus show that the strength of madrasas is that they have teacher resources with qualified teacher educational backgrounds; weaknesses, namely funding, are that the field could be narrower compared to the number of students. Opportunities include the existence of programs from the government for educational development, both for the development of teachers and school facilities and infrastructure, a religious community, as well as the high level of public interest in MAN and the geographical location of madrasas which facilitates community accessibility to education; and Challenges; it is shown that the challenges faced are competition with other schools in the same environment or nearby locations as well as increasingly complex societal demands and madrasah efforts to avoid moral degradation, especially the influence of information technology. In conclusion, Madrasah Aliyah Negeri 1 Tabalong implements strategic management through internal and external environmental analysis. Keywords: Implementation, Management, Madrasah, Strategy